Modeling Virus Mutation Dynamics Using Piecewise Fractional Derivatives (European Journal of Pure and Applied Mathematics, 2025)
A virus mutation model under piecewise fractional order derivatives involving Mittag-Leffler type kernel has been studied in this manuscript. As mutation is an important phenomenon for the survival of virus. The concerned study aims to detect the crossover behavior of the dynamics of virus mutation. The considered problem explains a compartmental model with pre and post mutation of virus. Fundamental results related to local and global stability of equilibrium points have been studied by using tools of nonlinear functional analysis. We have deduced positivity and feasibility of for the mentioned model using the fractional order derivatives. In addition, both trivial and non-trivial equilibrium points are computed and reproductive number is also derived. With the help of the considered numerical scheme based on Adam Bashforth method, we have simulated our results graphically for using different values of fractional order.
Keywords: Virus mutation model; Voltera- Lyapunov functions; piecewise derivative; Global stability; Numerical results